The space-temporal dimensión of the eros in the Phaedrus of Plato (Iter, 2022)
The second discourse of Sócrates in the Phaedrus succeeds in connecting its main themeM ith the previous two discourses -united through the use of the dual- by being an offering o fcompensation: so eros becomes finally the core of the three discourses. In this article eros isanalysed in its relation to the space of the universe and its capacity to enhance. consequently.the perception of time in man ’s soul. In the se circumst andes, love connects the hither o f thissensible Morid with the thither of the heavens as representaron of the inteligible, and becomestransformed in a transcendent power of spiritual ascent.
Keywords: Eros. love. cosmos. Plato